PERTANGGUNG JAWABAN PIDANA PERS MENURUT UNDANG-UNDANG NO 40 TAHUN 1999 DALAM TINDAK PIDANA PENCEMARAN NAMA BAIK - Oka Wijaya, I Kadek; Palguna, I Dewa Gede (Kertha Wicara : Journal Ilmu Hukum, 2015)
Paper titled press criminal liability under the Act No. 40 of 1999 in the crime of defamation. Workers press considers the imprisonment of journalists in the reform period is very restrict creativity press workers and a threat to freedom of expression as guaranteed in the Constitution and Law No. 40 of 1999 on the Press. Issues raised in this paper regarding the criminal responsibility by the negative press associated with the news as reported by him. The research method of this paper is normative research. The purpose of this paper to determine the criminal responsibility of the press. Based on Law No. 40 of 1999 on the Press in the event of prosecution, which is responsible for the editorial content of news is that the media in general, in this case represented by the Chief Editor (Editor in Chief). Accountability system press Act also may be charged to the company news. This criminal liability is known as "Vicarious Liability" (substitute criminal liabiability) sehubung thereto, affirmed in Article 12 of Law No. 14 of 1999 on the Press .
Keywords: Criminal Liability, Criminal Act, Defamation, Press